The Nature, Trends, Correlates, and Prevention of Mass Public Shootings in America, 1976-2020, (United States) - Fox, James Alan ([Verlag nicht ermittelbar], 2022)
Recent mass public shootings in venues as diverse as a school, a church, and a concert, have alarmed policymakers and the public alike. Despite mounting interest among journalists and academics, questions regarding the nature and prevention of mass shootings remain. For example, to what extent do mass shooters have histories of mental illness, substance abuse, or violence? Does strengthening or weakening gun control laws have an impact on the incidence or severity of mass public shootings? Are mass shooters influenced by media coverage of these events? This study is comprised of seven datasets that contain information on mass shooting incidents between 1976 and 2020. Mass public shootings were defined as any event in which four or more individuals, not including the assailant(s), were killed by gunfire in a public setting within a 24-hour period, absent any associated criminal activity (such as a robbery, gang conflict, or illicit drug trade). Three of the datasets have information on characteristics of mass shooting incidents, offenders, victims; two have information on media coverage surrounding these events; and two have information on averted or thwarted mass shooting incidents.